THE IMPACT OF KETOGENIC DIETS ON WEIGHT LOSS IN ADULTS: A SYSTEMATIC REVIEW OF RANDOMIZED CONTROLLED TRIALS AND META-ANALYSES - Adamczyk, Justyna; Gawęda, Wojciech; Łobodzińska, Wiktoria; Ficek, Maciej (International Journal of Innovative Technologies in Social Science, 2026)
Purpose: This systematic review aimed to evaluate the efficacy of ketogenic diets for weight loss in adults by examining evidence from randomized controlled trials and meta-analyses published between 2015 and the present.Methodology: A comprehensive review was conducted  based on 20 articles retrieved from PubMed, focusing on randomized controlled trials (RCTs) and meta-analyses investigating the impact of ketogenic diets on weight loss in adult populations with various health conditions. The reviewed studies compared ketogenic diets with energy-restricted diets, low-fat diets, and the Mediterranean diet, with intervention durations ranging from short-term to one year.Findings: The findings from RCTs suggest that ketogenic diets can be more effective for short to medium-term weight loss compared to standard energy-restricted diets in obese adults . While some trials showed comparable weight loss between healthy low-fat and low-carbohydrate diets over a year , others indicated a slight advantage for low-carbohydrate approaches. Ketogenic diets also demonstrated effectiveness in specific populations, such as overweight adults with type 2 diabetes or prediabetes , older adults with obesity , and individuals with NAFLD. Meta-analyses corroborated the efficacy of ketogenic diets for weight loss in overweight and obese adults , with very low-calorie ketogenic diets showing significant short-term weight loss and potential for sustained weight loss . The mechanisms likely involve appetite regulation and increased fat oxidation. Ketogenic diets generally lead to reductions in fat mass, with variable effects on lean mass depending on the population and study design.Conclusions: Ketogenic diets can be an effective strategy for weight loss, particularly in the short to medium term for obese and overweight adults, and may offer benefits for specific populations with metabolic conditions. While their long-term superiority over other well-designed diets is not consistently demonstrated, the evidence supports their role in reducing fat mass. Careful consideration of individual health status, dietary adherence, and potential side effects is warranted when implementing ketogenic diets for weight management.